2006
DOI: 10.1097/01.brs.0000231442.05245.87
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Human Mesenchymal Stem Cells With Disc Cells

Abstract: Addition of MSCs to AF cells resulted in an up-regulation of the proteoglycans synthesis. This study provides the rationale for further investigation of the potential of MSC therapy in treating intervertebral disc degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 12 publications
(10 reference statements)
6
57
0
2
Order By: Relevance
“…Furthermore, MSCs stimulate tissue-associated stem cells to differentiate to target tissues . Le Visage et al (2006) found that proteoglycan synthesis increased when MSCs were co-cultured with annulus fibrosus cells, and Sakai et al (2006) reported increased proteoglycan and extracellular annulus fibrosus matrix synthesis, and the restoration of water disc height after transplanting MSCs into IVDs in an rabbit model, which was similar to that found by Sakai et al (2006).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, MSCs stimulate tissue-associated stem cells to differentiate to target tissues . Le Visage et al (2006) found that proteoglycan synthesis increased when MSCs were co-cultured with annulus fibrosus cells, and Sakai et al (2006) reported increased proteoglycan and extracellular annulus fibrosus matrix synthesis, and the restoration of water disc height after transplanting MSCs into IVDs in an rabbit model, which was similar to that found by Sakai et al (2006).…”
Section: Discussionsupporting
confidence: 69%
“…However, these approaches cannot be viewed as fundamental treatments for IVD degeneration because they do not address its cause. Recently, the molecular biological characteristics of IVD degeneration were identified, and treatment strategies are being sought that regenerate IVDs by restoring extracellular matrix or cellular components in animal models (Crevensten et al 2004;Le Visage et al 2006;Sakai et al 2006Sakai et al , 2005Sakai et al , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…At this early stage, matrix loss is still limited or partial and there is no need to replace the bulk matrix. As a result, minimally invasive treatments such as injecting growth factors to stimulate the NP cells to synthesize proteoglycans [74] or injecting cells able to synthesize appropriate ECM such as bone marrow mesenchymal stem cells [48,67,108] are the most commonly proposed. Nevertheless, one important inadequacy of this approach is that the high disc pressure and the aqueous nature of the cell suspension usually result in depletion of the local availability of cells [5,53].…”
Section: Scaffolding In Intervertebral Disc Tissue Engineeringmentioning
confidence: 99%
“…6,7,35 Recent attempts to supplement the disk's regenerative capabilities and prevent tissue degradation have already shown promising results using both cell-based and gene therapeutic approaches. [54][55][56] Furthermore, an elegant therapy approach that would directly address and neutralize the apoptosis-inducing ligand TRAIL might help to at least delay progression of disk degeneration. A comparable approach that involves FasL function perturbing antibodies has already shown promising results in the regeneration and functional recovery after spinal cord injury in an animal model.…”
Section: Discussionmentioning
confidence: 99%